2017
DOI: 10.1080/09585192.2017.1314314
|View full text |Cite
|
Sign up to set email alerts
|

Unpredictable working time, well-being and health in the police service

Abstract: The unpredictability of working time is a seldom studied, but increasingly prominent, feature of employment across occupations, including those where nonstandard or unsocial hours have become the norm. This paper proposes that unpredictability which is driven by employer demands for flexibility (e.g. scheduling practices) is associated with greater employee work-life conflict and perceived stress. This, in turn, has implications for health behaviour (alcohol consumption, sleep disturbance) and symptoms (digest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 76 publications
(74 reference statements)
1
31
0
1
Order By: Relevance
“…Studies examining the relationship between WLC and alcohol use have demonstrated both a positive indirect relationship (Frone et al, ; Leineweber, Baltzer, Magnusson Hanson, & Westerlund, ; Wang et al, ) and direct relationship (Frone et al, ; Scholarios, Hesselgreaves, & Pratt, ; Wolff, Rospenda, Richman, Liu, & Milner, ) between the two. Of the studies that indirectly relate WLC to alcohol use, psychological strain has been offered as a possible mediator.…”
Section: Health Behaviorsmentioning
confidence: 99%
“…Studies examining the relationship between WLC and alcohol use have demonstrated both a positive indirect relationship (Frone et al, ; Leineweber, Baltzer, Magnusson Hanson, & Westerlund, ; Wang et al, ) and direct relationship (Frone et al, ; Scholarios, Hesselgreaves, & Pratt, ; Wolff, Rospenda, Richman, Liu, & Milner, ) between the two. Of the studies that indirectly relate WLC to alcohol use, psychological strain has been offered as a possible mediator.…”
Section: Health Behaviorsmentioning
confidence: 99%
“…Unpredictable working hours show a strong correlation with WFC [ 19 20 ], and WFC can cause sleep disturbance [ 21 ]. Furthermore, stress-mediated mechanisms could also be considered because changes in WTA can increase stress when applied with low control in a job demand-control model [ 13 ], and unpredictable schedules are known to increase perceived stress in practice [ 22 ]. It is well established that stress causes sleep disturbance through over-activation of the hypothalamic-pituitary-adrenal (HPA) axis and increased sympathetic tone [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Across definitions, however, previous findings have consistently shown work schedule unpredictability to be related to worse outcomes for workers and families. Compared to workers with predictable work schedules, those with unpredictable work schedules report more psychological distress, worse sleep quality, and worse physical health (Schneider & Harknett, 2019; Scholarios, Hesselgreaves, & Pratt, 2017). Unpredictable work schedules also correlate with important family functioning outcomes, including higher parenting stress and lower‐quality parent–child interactions (Henly et al, 2006; Schneider & Harknett, 2016).…”
Section: Theoretical Linkages Between Parents' Work Schedule Unpredicmentioning
confidence: 99%